From the Republic of the Rio Grande A Personal History of the Place and the People - de la Garza, Beatriz (University of Texas Press, 2021)
The Republic of the Rio Grande had a brief and tenuous existence (1838-1840) before most of it was reabsorbed by Mexico and the remainder annexed by the United States, yet this region that straddles the Rio Grande has retained its distinctive cultural identity to the present day. Born on one side of the Rio Grande and raised on the other, Beatriz de la Garza is a product of this region. Her birthplace and its people are the subjects of this work, which fuses family memoir and borderlands history. From the Republic of the Rio Grande brings new insights and information to the study of transnational cultures by drawing from family papers supplemented by other original sources, local chronicles, and scholarly works. De la Garza has fashioned a history of this area from the perspective of individuals involved in the events recounted. The book is composed of nine sections spanning some two hundred years, beginning in the mid-1700s. Each section covers not only a chronological period but also a particular theme relating to the history of the region. De la Garza takes a personal approach, opening most sections with an individual observation or experience that leads to the central motif, whether this is the shared identity of the inhabitants, their pride in their biculturalism and bilingualism, or their deep attachment to the land of their ancestors